Medicinal Plant Extracts and Natural Compounds for the Treatment of Cutaneous Lupus Erythematosus: A Systematic Review - Lubov, Janet E.; Jamison, Aisha S.; Baltich Nelson, Becky; Amudzi, Alice A.; Haas, Kelly N.; Richmond, Jillian M. (Frontiers in Pharmacology, 2022)
Cutaneous lupus erythematosus (CLE) is a group of autoimmune connective tissue disorders that significantly impact quality of life. Current treatment approaches typically use antimalarial medications, though patients may become recalcitrant. Other treatment options include general immunosuppressants, highlighting the need for more and more targeted treatment options. The purpose of this systematic review was to identify potential compounds that could be repurposed for CLE from natural products since many rheumatologic drugs are derived from natural products, including antimalarials. This study was registered with PROSPERO, the international prospective register of systematic reviews (registration number CRD42021251048). We comprehensively searched Ovid Medline, Cochrane Library, and Scopus databases from inception to April 27th, 2021. These terms included cutaneous lupus erythematosus; general plant, fungus, bacteria terminology; selected plants and plant-derived products; selected antimalarials; and JAK inhibitors. Our search yielded 13,970 studies, of which 1,362 were duplicates. We screened 12,608 abstracts, found 12,043 to be irrelevant, and assessed 565 full-text studies for eligibility. Of these, 506 were excluded, and 59 studies were included in the data extraction. The ROBINS-I risk of bias assessment tool was used to assess studies that met our inclusion criteria. According to our findings, several natural compounds do reduce inflammation in lupus and other autoimmune skin diseases in studies using in vitro methods, mouse models, and clinical observational studies, along with a few randomized clinical trials. Our study has cataloged evidence in support of potential natural compounds and plant extracts that could serve as novel sources of active ingredients for the treatment of CLE. It is imperative that further studies in mice and humans are conducted to validate these findings. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=251048.